Experimental investigation of ultrasonic vibration-assisted cryogenic minimum quantity lubrication for milling of Ti-6Al-4V and grinding of Zerodur - Blasl, Jacqueline; Lichtinger, Klaus; Vieltorf, Fabian; Zaeh, Michael F.; Hanenkamp, Nico (Production Engineering, 2023)
Increasing demands on component properties are leading to the development of high-performance materials for which conventional production methods are reaching their limits from an economic and ecological point of view. In recent years, two technologies have been developed that show great potential compared to conventional machining processes, particularly in machining high-performance materials such as the titanium alloy Ti-6Al-4V. Ultrasonic-assisted machining leads to reduced cutting forces and increased tool life. Cryogenic minimum quantity lubrication prevents the occurrence of high machining temperatures and allows higher material removal rates without a negative impact on tool life. This paper shows the influence of ultrasonic-assisted milling and grinding processes in combination with cryogenic minimum quantity lubrication on the machinability of the high-strength materials Ti-6Al-4V and Zerodur. The investigation addressed cutting forces, tool wear, and surface roughness. The superposition of the technologies resulted in longer tool life and lower tool wear for both milling and grinding. However, the surface roughness was consistently higher due to the ultrasonic superposition. Nevertheless, machining with ultrasonic vibration-assisted cryogenic minimum quantity lubrication has great potential for difficult-to-machine materials, especially due to the reduction in tool wear.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Cryogenic cooling; Minimum quantity lubrication; Ti-6Al-4V; Ultrasonic vibration; Vibration-assisted machining; Zerodur